Developing the Performance of the Saudi Ministry of Education’s Institutional Innovation System in Light of The EFQM Innovation Lens - Althnian, Fatmah Abdullah (The Arab Journal of Administration, 2024)
The dissertation aims to provide a proposal to develop the performance of the Saudi Ministry of Education’s institutional innovation system in Light of the European model of innovation lens through analyzing the most important global experiences that can be benefited from. It is purpose is to develop the performance of the institutional innovation system in the Saudi Ministry of Education, revealing the reality of the performance of the institutional innovation system in the Saudi Ministry of Education, in the light of the European form of the innovation lens, and through identifying requirements for developing the performance of the institutional innovation system in the Saudi Ministry of Education, in the light of the European form of the innovation lens. The descriptive approach is applied through documentary and surveying methods. The questionnaire and interviews are the study tools. The Study Society is the undersecretaries of the Ministry of Education, And The leaders of the Ministry of Education. The study reached a number of results are: The performance of the Saudi Ministry of Education’s institutional innovation system in the light of the European form of innovation lens achieved generally an average performance rate. The requirements for developing the performance of the institutional innovation system in the Saudi Ministry of Education, in the light of the European form of the innovation lens are between (40%-100%), in which the most prominent thereof are: Establishing a strategic plan for the institutional innovation related to the Ministry of Education’s strategy. Another essential requirement is developing an effective system to manage the organizational knowledge supporting knowledge-share among employees.